2019
DOI: 10.1038/s41598-018-37962-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SMALP co-extracted phospholipids shows distinct membrane environments for three classes of bacterial membrane protein

Abstract: Biological characterisation of membrane proteins lags behind that of soluble proteins. This reflects issues with the traditional use of detergents for extraction, as the surrounding lipids are generally lost, with adverse structural and functional consequences. In contrast, styrene maleic acid (SMA) copolymers offer a detergent-free method for biological membrane solubilisation to produce SMA-lipid particles (SMALPs) containing membrane proteins together with their surrounding lipid environment. We report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 52 publications
(59 reference statements)
3
54
0
Order By: Relevance
“…When studying endogenously expressed protein, the physiological accuracy of SMALPs is improved over other systems, as the solubilised protein is isolated with a sample of mixed lipid species, representative of the membrane into which the protein was expressed. Coupled with lipidomics, this has helped to delineate the different lipid environments within a cell and their relevance for protein function [ 289 , 290 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…When studying endogenously expressed protein, the physiological accuracy of SMALPs is improved over other systems, as the solubilised protein is isolated with a sample of mixed lipid species, representative of the membrane into which the protein was expressed. Coupled with lipidomics, this has helped to delineate the different lipid environments within a cell and their relevance for protein function [ 289 , 290 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…While a reconstitution approach provides for a controlled and defined lipid environment, the necessity of an initial detergent-based extraction step may disrupt protein-lipid interactions integral to the structural integrity of transmembrane segments. In contrast with nanodisc reconstitution, SMA copolymers extract membrane proteins directly from the lipid bilayer, eschewing detergent entirely and permitting the study of membrane proteins in the presence of endogenous lipids (51, 52) and, in principle, maintaining the protein-lipid interactions that occur at the cell membrane (53).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the lipid fingerprint of yeast membranes depends on growth conditions such as temperature, carbon source and oxygen supply, and these could contribute to the quantitative difference observed between studies [ [51] , [52] , [53] ]. Furthermore, it was previously shown that SMA solubilisation is not preferential for any particular lipid subset [ [13] , [14] , [15] , 54 ]. Nevertheless, in SMA-solubilised membranes we have observed loss of the signals for sphingomyelin (d36:3) and triacylglycerol, higher diversity of phosphatidylethanolamine and phosphatidylserine lipids, and the change in signal intensities of phosphatidylcholine lipids while their heterogeneity remained the same.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that specific lipid environments are important not just for stability of many proteins but also for their function [ [10] , [11] , [12] ], including CD81. In recent years an alternative approach to detergents has been developed using styrene maleic acid co -polymer (SMA), which extracts membrane proteins with their surrounding lipids [ [13] , [14] , [15] ]. The SMA polymer inserts into a membrane and extracts a disc of lipid bilayer with the polymer wrapping around the outer edge [ 16 ].…”
Section: Introductionmentioning
confidence: 99%